The focal group as a technique for data collection and analysis in qualitative research: DOI: 10.15343/0104-7809.2011354438442 - Stein Backes, Dirce (2011)
The focal group constitutes an important technique for data collection in qualitative research. With the aim of extending itsuse and to constitute the participants as active subjects of nursing research, the present study aimed at examining the focal group as atechnique for data collection and analysis of qualitative data. Such proposal represents a new methodological strategy for qualitativeresearch, in addition to being a possibility to instigate new knowledge, ressignify professional attitudes and to approach research ofthe settings of practice and vice versa.